"Everything comes together": Students' collaborative development of a professional dialogic practice in architecture and design education. (September 2020) - Davidsen, Jacob; Ryberg, Thomas; Bernhard, Jonte
Highlights: Students' ways of integrating historical bodily-material resources are important aspects of developing a professional dialogic practice. Professional dialogical practice is composed of bodily, material and historical resources in interaction. Embodied interaction analysis provides a stance for viewing how students are developing a professional dialogic practice in action. Abstract: Previous studies of engineering and design students found that they are less competent than professionals in managing iterative processes, working with ill-structured problems and integrating objects and materials into their design process. Accordingly, there is a broad interest in understanding how students learn to design collaboratively and how they are becoming professionals. In this paper, we explore how a group of architectural engineering students are collaboratively developing a dialogic practice, which resembles how professionals work. We base this analysis on video extracts of a group of students preparing for a formal design review session by asking: What are the characteristics of students' dialogic practice in a collaborative design project? Does it develop into a professional dialogic practice? Based in embodied interaction analysis of the video extracts, we show how this professional dialogical practice is developed using bodily, material and historical resources, rather than only being manifested in verbal discourse. We argue that mastering these dialogic practices is an important part of becoming a professional. Our analysis shows that the students are oriented to the tactile and kinaesthetic aspects of their collaborative work, they engage in collaborative embodied design activities and they integrate the history of the design process by repurposing materials in their current activity. We also argue that our methodological orientation to the students' interactional work allows us to see how they develop a dialogic practice better than existing studies using protocol analysis.